PENGARUH METODE PEMBERIAN TUGAS BERBASIS HOTS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV - Diana, Diana; Alannasir, Wahyullah (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2023)
The purpose of this study was to determine the implementation of the HOTS-based assignment method, the learning outcomes of fourth grade students before and after the use of the HOTS-based assignment method and the effect of using the HOTS-based assignment method on mathematics learning outcomes for fourth grade students MI AL-IKHLAS Buntu Podong Kec.. Masalle Kab. Enrekang. This research is an experimental research with a quasi-experimental type of research. The implementation of the HOTS-based assignment method for fourth grade students at SD MI Al-Ikhlas Buntu Podong, Masalle District, Enrekang Regency, which was carried out face to face, was well implemented. Evidenced by the increase in the implementation of the HOTS-based assignment method on the teacher's observation sheet is in the very good category and on the student's observation result sheet it is also included in the very good category. Mathematics learning outcomes using the HOTS-based assignment method for fourth grade students at SD MI Al-Ikhlas Buntu Podong Enrekang Regency, namely the average score in the posttest is higher with an average of 83.33 compared to the average pretest score of learning outcomes, namely achieving 55.00. There was a significant increase in the average value of learning outcomes, namely reaching 28.33 with a percentage of 30%. The use of the HOTS-Based Assignment Method has an effect on the learning outcomes of Class IV students of SD MI Al-Ikhlas Buntu Podong, Masalle District, Enrekang Regency. This can be seen from the hypothesis test or independent sample T-Test obtained 0.00 so that the value is 0.000 <0.05. It can be seen that there is a significant effect on the mathematics learning outcomes of Class IV students of SD MI Al-Ikhlas Buntu Podong, Masalle District, Enrekang Regency.